The Dual Dimension of Consciousness: Environment and Health as Predictors of Environmentally Friendly Behavior - Awingan, Joan S.; Wu, Shi ching (Cahaya Ilmu Cendekia Publisher, 2025)
Purpose of the study: This study was conducted to determine the influence of environmental and health awareness on people's pro-environmental behavior. Methodology: The subjects in this study were 203 residents of Tondo District, Manila, Philippines, selected using non-probability sampling and accidental sampling techniques. Confirmatory Factor Analysis (CFA) was used to test the validity of the measuring instrument, and Multiple Regression Analysis was used to test the research hypotheses. Main Findings: The results of the study indicate that there is a joint influence of environmental awareness and health on the pro-environmental behavior of people living in Tondo District, Manila, Philippines. The results of the minor hypothesis test indicate that general belief, personal attitude and health self-monitoring have a significant influence on Pro-environmental. The results also show that the proportion of Pro-environmental variance explained by all independent variables is 26.9%, while the remaining 73.1% is influenced by other variables outside this study. Novelty/Originality of this study: The novelty of this study lies in its integrated examination of environmental awareness and health as dual predictors of pro-environmental behavior in society. Unlike previous studies that focused solely on the ecological or health dimensions, this research offers a holistic perspective, highlighting how shared awareness influences people's sustainable actions in their daily lives.